Vitamin D receptor genotype rs731236 (Taq1) and breast cancer prognosis - Perna, Laura (Cancer epidemiology, biomarkers & prevention, 2013)
Several studies have suggested that the anticancerogenous effects of vitamin D might be modulated by genetic variants in the vitamin D receptor (VDR) gene. The association of VDR polymorphisms with breast cancer-specific and all-cause mortality after a breast cancer diagnosis remains, however, largely unexplored. We assessed the association of genetic variants in VDR (rs731236, rs1989969, rs2228570, and 11568820) with breast cancer survival in a sample of 498 patients with breast cancer with a mean age at diagnosis of 61 years from Saarland, Germany, who were followed for up to 5 years with respect to total and breast cancer-specific mortality (56 and 48 events, respectively). Adjusted HRs with 95% confidence intervals (CI) were estimated by Cox regression models. We found that patients with breast cancer homozygous for the rare allele of rs731236 (15% of the women in our cohort) had a tendency toward an increased risk for breast cancer-specific mortality. The HR (95% CI) adjusted for age and breast cancer stage was 2.8 (1.1-7.2) for breast cancer-specific mortality and 2.1 (0.9-4.9) for total mortality. Additional adjustment for family history of breast cancer, radical mastectomy, and body mass index only marginally changed the estimates. No association was found for rs1989969, rs2228570, and rs11568820. Our analysis suggests that VDR polymorphism rs731236 might be associated with breast cancer-specific mortality, and if our findings are confirmed in future bigger studies rs731236 might deserve consideration as a prognostic factor in clinical care of patients with breast cancer.